Managing customer service - Grant, David (Henry Stewart Talks, 2010)
Concepts of customer service, A satisfied customer: the common denominator between marketing and logistics, Customer service measurement and metrics, Eight criteria for a good customer service metric, Logistics and marketing, Logistics activities are services, Logistics customer service and quality strategies, A logistics service quality model